2020
DOI: 10.1007/s00167-020-06073-7
|View full text |Cite|
|
Sign up to set email alerts
|

Footprint preparation with nanofractures in a supraspinatus repair cuts in half the retear rate at 1-year follow-up. A randomized controlled trial

Abstract: Purpose To evaluate if adding nanofractures to the footprint of a supraspinatus tear repair would have any effect in the outcomes at one-year follow-up. Methods Multicentric, triple-blinded, randomized trial with 12-months follow-up. Subjects with isolated symptomatic reparable supraspinatus tears smaller than 3 cm and without grade 4 fatty infiltration were included. These were randomized to two groups: In the Control group an arthroscopic supraspinatus repair was performed; in the Nanofracture group the foot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(55 citation statements)
references
References 20 publications
0
54
0
1
Order By: Relevance
“…Recently, Toro et al 23 conducted an RCT comparing intraoperative microfracture with a control, which also showed no statistical difference between groups in rotator cuff healing rates as well as Constant and ASES scores. A recent study by Ruiz Ibán et al 20 demonstrated a significantly lower retear rate of 19.4% in the nanofracture group versus 42.4% in the control group. In this latter study, a disposable device with a 1 mm–thick needle was used to perform microfracture.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Recently, Toro et al 23 conducted an RCT comparing intraoperative microfracture with a control, which also showed no statistical difference between groups in rotator cuff healing rates as well as Constant and ASES scores. A recent study by Ruiz Ibán et al 20 demonstrated a significantly lower retear rate of 19.4% in the nanofracture group versus 42.4% in the control group. In this latter study, a disposable device with a 1 mm–thick needle was used to perform microfracture.…”
Section: Discussionmentioning
confidence: 90%
“…The results of this study do not support our hypothesis that bone channeling at the time of rotator cuff repair results in a lower retear rate and superior functional outcomes. The channeling technique has been described using other terms in the literature including microfracture, 16,17 crimson duvet, 23 and nanofracture, 20 but the procedure is fundamentally the same. The instruments used in RCTs investigating intraoperative bone channeling in arthroscopic rotator cuff repair produce channels that range from 1 to 1.5 mm in width and from 3 to 9 mm in depth, making them similar to those used in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, this special tunnel-based “footprint preparation” using bone tunnel with a larger refreshed bone bed contact area in the Plug-Pat may lead to an increased local outflow of stem cells and other cytokines from the bone marrow for better introduction to the healing interface, thus enhancing graft-to-bone healing. 12,14,25,34,39 Furthermore, the mechanical stimulation of tensile stress along the intratunnel graft tendon may be related to improved tenogenesis, intratendinous remodeling, and cell orientation at the graft-bone interface in the Plug-Pat. 3,8,32,55 Similar findings were observed in previous studies that compared these 2 fixations using the rotator cuff tendon or patellar tendon.…”
Section: Discussionmentioning
confidence: 99%
“…La creación de microperforaciones en la huella humeral antes de la reparación tendinosa permite mejorar el entorno biológico aportando un mayor flujo local de células madre y de otros factores que favorecen la cicatrización del tendón. 12 Sin embargo, esta técnica quedaría desaconsejada cuando la cabeza humeral es muy osteoporótica, porque existe el riesgo de debilitar aún más el hueso y producir una falla del anclaje del tendón al hueso.…”
Section: Microperforacionesunclassified